Pendampingan Orang Tua dan Pengaruhnya terhadap Minat Belajar Baca Tulis Alquran Siswa MIN 1 Dairi - Muhammad Sanif (Journal on Education, 2024)
This research aims to identify the low level of parental assistance to children, the lack of parental attention which makes children's interest and enthusiasm for learning low and the low interest in learning to read and write the Quran due to lack of assistance from parents. This research is quantitative research. This research uses a "Simple Random Sampling" sampling technique using two variables. First, parental assistance as a variable (X), second, interest in learning to read and write the Quran as a variable (y), with the instruments in this research in the form of questionnaires and documentation. With questionnaire data collection techniques (questionnaires) and documentation. Meanwhile, data analysis techniques use statistical methods. The results of the study show that the results of this study prove the alternative hypothesis (Ha) proposed by the researchers, namely "there is a significant influence between parental assistance on the interest in learning to read and write the Koran of MIN 1 Dairi students", which was accepted. Meanwhile, the null hypothesis (Ho) "there is no significant influence between parental assistance on interest in learning to read and write the Koran of MIN 1 Dairi students", was rejected.